2013
DOI: 10.1089/lap.2012.0410
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Shoulder Pain Following Laparoscopic Cholecystectomy: A Prospective, Randomized, Controlled Trial

Abstract: Active aspiration of the residual gas just before the removal of the trochars is a simple procedure and leads to a more comfortable hospital stay for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…In particular, preventing and managing carbon dioxide pneumoperitoneum-induced shoulder pain is important during laparoscopic surgery under regional anesthesia. Postoperative shoulder tip pain resulting from diaphragm irritation after general anesthesia can be easily reduced by removing intra-abdominal residual carbon dioxide gas, which can be accomplished by applying active aspiration via the trochars [12] or the lung recruitment maneuver at the end of surgery [13]. However, intraoperative shoulder tip pain during regional anesthesia is a leading cause of conversion to general anesthesia [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, preventing and managing carbon dioxide pneumoperitoneum-induced shoulder pain is important during laparoscopic surgery under regional anesthesia. Postoperative shoulder tip pain resulting from diaphragm irritation after general anesthesia can be easily reduced by removing intra-abdominal residual carbon dioxide gas, which can be accomplished by applying active aspiration via the trochars [12] or the lung recruitment maneuver at the end of surgery [13]. However, intraoperative shoulder tip pain during regional anesthesia is a leading cause of conversion to general anesthesia [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…The pain scores of the patients and the analgesic requirements were significantly decreased. Das et al 9 performed a similar study and also reported decreased pain scores.…”
Section: Reducing Residual Gas After Lcmentioning
confidence: 74%
“…12 Various methods have been investigated with the aim of decreasing shoulder pain. 4,5,[7][8][9][12][13][14] One of the methods that has been studied is active gas suction. Jorgensen et al 8 studied the effect of applying suction on the suprahepatic drain after LC and concluded that this procedure significantly reduced shoulder pain as reported by the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst all the discomforts, carbon dioxide pneumoperitoneum-induced shoulder pain during laparoscopic surgery under spinal anaesthesia is the most distressing. Postoperative shoulder tip pain after general anaesthesia is easily managed by removing intra-abdominal residual carbon dioxide by applying active aspiration via the trocars [8] or by lung recruitment manoeuvre. [9] However, intraoperative shoulder tip pain during regional anaesthesia is a leading cause of conversion to general anaesthesia.…”
Section: Time (Postoperative)mentioning
confidence: 99%